O oncologista clínico diante da morte: implicações para a produção do cuidado - Campos, Christine de Medeiros Francilaide (2011)
It is undeniable that all the extraordinary technological advances in contemporary society have increased the severe patients expectation and quality of life, especially cancer patients. On the other hand, it is easily verifiable by many researches that it was not possible to advance in the same proportion in caring for the human experience of death. Much is said about the anguish of a man facing death, of cancer patients in terminal stage, about their families, and very little about the feelings, anxieties and ways of coping with the medical professional who deals with this situation, specifically the clinical oncologist. Little is known about the experience of the doctor who has learned to take death as an enemy to be defeated, and increasingly is compelled to live at length with his advertisement. However, we started to watch in recent years a growing interest of researchers in this issue. This study seeks to add to this interest in order to understand the experience of clinical oncologists that accompany dying patients, the meanings they attach to death, ways of coping and the implications for providing care. This is a qualitative study in which was used as a tool for data collection an in-depth interview with the projective using script and scenes. Gadameriana Hermeneutics was used for analysis and interpretation of narratives. The subjects were 10 clinical oncologists who work at two institutions from cancer treatments in the state of Rio Grande do Norte, chosen from a variation in the time working in the specialty (minimum of one year, even old ones). However, you can bring some initial results for the dialogue. It was found that the death is still a topic that causes many difficulties in the daily lives of these professionals, the choice for oncology involves dealing with death without preparation in medical education; being close to the patient in the final moment, supporting the family, coping with own pain of loss and the inability to heal. These are central elements of the narratives. We also have investment in medical training and continuing education in setting up a demand that permeates the discourse of participants. Being able to listen to the subjective world of clinical oncologists will support the work not only for them as other professionals who deal with patients with advanced cancer, providing evidence to understand to what extent the meanings attributed to its know-how before patients on the verge of death interfere with the production of care and allow identify coping strategies in everyday life of these professionals that hinder or facilitate coping with death, promote or preclude the care with others and with themselves. It is hoped that research can contribute to the field of knowledge about the know-how in clinical oncology and their terminal-care-death oncologist-patient relationships, bringing runways capable of promoting a better quality of care in the production of all involved in this process: professionals, patients and families